2017
DOI: 10.1016/j.addr.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and physical vessel modulation strategies to improve EPR-mediated drug targeting to tumors

Abstract: The performance of nanomedicine formulations depends on the Enhanced Permeability and Retention (EPR) effect. Prototypic nanomedicine-based drug delivery systems, such as liposomes, polymers and micelles, aim to exploit the EPR effect to accumulate at pathological sites, to thereby improve the balance between drug efficacy and toxicity. Thus far, however, tumor-targeted nanomedicines have not yet managed to achieve convincing therapeutic results, at least not in large cohorts of patients. This is likely mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
165
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(165 citation statements)
references
References 93 publications
0
165
0
Order By: Relevance
“…NP accumulation in tumors is a complex phenomenon, governed both by NP characteristics such as size, charge, and surface chemistry, as well as tumor properties such as vascular density, permeability, cell density, stromal content, etc . Heterogeneity in TME, even within tumors of same molecular subtype, poses a barrier to delivery and hence, therapeutic efficacy of macromolecular drugs such as antibodies and NPs.…”
Section: Resultsmentioning
confidence: 99%
“…NP accumulation in tumors is a complex phenomenon, governed both by NP characteristics such as size, charge, and surface chemistry, as well as tumor properties such as vascular density, permeability, cell density, stromal content, etc . Heterogeneity in TME, even within tumors of same molecular subtype, poses a barrier to delivery and hence, therapeutic efficacy of macromolecular drugs such as antibodies and NPs.…”
Section: Resultsmentioning
confidence: 99%
“…It has been well demonstrated that abnormal tumor vessels often grow rapidly to meet the nutrient demand to maintain tumor progression [141]. In this regard, disrupting the abnormal vascular system in TME could deplete the nutrition supply and induce tumor regression.…”
Section: Nanoparticle-based Strategiesmentioning
confidence: 99%
“…Rational designs of nanomedicine aid in overcoming physiological barriers of solid tumors for achieving enhanced therapeutic efficacy, including manipulating physical, chemical, and biological properties of nanoparticles . Negatively charged nanoparticles (NPs) are very stable in the blood circulatory system, thereby allowing NPs accumulation in tumors through enhanced permeability and retention effects . It has been reported that the optimized size may also improve the delivery efficiency in tumors and NPs with moderate rigidity could enhance the multibiological barrier penetrating capability for drug delivery in comparison with their soft and hard counterparts .…”
Section: Methodsmentioning
confidence: 99%